Protective Effect of Uvaria narum Bl. Leaves on Carbon Tetrachloride induced Hepatotoxicity in Rats - Jagir R. Patel, Moses Samuel Rajan, Shenoy Ashok, Shabaraya A. R (Journal of Applied Pharmaceutical Science, 2013)
In the present study, Uvaria narum (Annonaceae) leaves were evaluated for its possible hepatoprotective potential. Elevation in hepatic biomarkers like SGPT, SGOT, ALP, bilirubin & other biochemical parameters like Cholesterol, triglycerides, urea & tissue LPO, where as decrease in total protein, albumin, glucose & tissue GSH, CAT, SOD was observed in CCl4 induced liver toxicity. Treatment with Silymarin, UNLE-200 and UNLE -400 resorted the altered hepatic biomarkers and biochemical parameters significantly in dose dependent manner. The biochemical observations were supplemented by histopathological examinations of liver sections. Relative organ weights were also reduced dose dependently in extract treated rats. Overall observations indicates that UNLE exerted remarkable hepatoprotective efficacy against CCl4 induced liver damage were comparable to reference standard Silymarin (100mg/kg) that is, may be due to its augmenting endogenous antioxidant mechanisms. These findings suggest the use of plant for treatment of liver diseases in oriental traditional medicine.
Keywords: CCl4, silymarin, UNLE-U.narum leaf extract, Hepatopr